1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Prove cos(sin^-1 x)= [itex]\sqrt{1-x}[/itex]

  1. May 29, 2012 #1
    1. The problem statement, all variables and given/known data

    cos(sin-1x) = [itex]\sqrt{1-x^2}[/itex]

    2. Relevant equations

    I would assume trigonometrical identities would be used to prove this.
     
  2. jcsd
  3. May 29, 2012 #2
    Hello nowayjose! :smile:

    Yes, they would...

    Why don't you start by assuming [itex]\theta = sin^{-1}x[/itex], and then draw out a triangle to find a relation between theta and cosine, that you can use...

    PS : your thread title is misleading :uhh:
     
  4. May 29, 2012 #3
    Thanks for the prompt reply!
    Sorry, and the question's undoubtedly stupid. I've used this method before and haven't happened to used any identities (or so i believe...).

    [itex]\theta = sin^{-1}x[/itex]
    [itex]sin\theta = x[/itex]
    [itex] sin = 1/X [/itex]
    the cosine side must therefore be [itex]\sqrt{1-x^2}[/itex]
    therefore the cosine angle is
    [itex]\sqrt{1-x^2} / 1[/itex]
     
  5. May 29, 2012 #4

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    Or, different wording of the same idea: [itex]sin^2(\theta)+ cos^2(\theta)= 1[/itex] so that [itex]cos(\theta)= \pm\sqrt{1- sin^2(\theta)}[/itex]. So
    [tex]cos(sin^{-1}(x))= \pm\sqrt{1- sin^2(sin^{-1}(x)}= \pm\sqrt{1- x^2}[/tex]
     
  6. May 29, 2012 #5

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    What you have written here makes little sense. If [itex]\theta= sin^{-1}(x)[/itex] then, yes, [itex]sin(\theta)= x[/itex], but you cannot write "sin" without some argument. And the "-1" does NOT indicate reciprocal (1/x), it means the inverse function.
     
  7. May 30, 2012 #6
    consider the attached triangle picture (sorry its sloppy)

    in that case Sin(theta) = x (hypotenuse is 1, opposite is x)

    thus sin^-1(x) = theta.

    For that same theta, using a^2 + b^2 = c^2......

    x^2 + b^2 = 1^2
    b^2 = 1-x^2
    b = sqrt( 1 - x^2)

    and cos(theta) = adj / hyp
    so,
    cos(theta) = sqrt( 1 - x^2) / 1
    cos(theta) = sqrt( 1 - x^2)


    recall:
    sin^-1(x) = theta

    so sub in theta


    cos(sin^-1(x)) = sqrt( 1 - x^2)


    Proved!
     

    Attached Files:

  8. May 30, 2012 #7
    People sorry for the typo and for not being clear about my thought process.

    Bascially what i meant was:

    [itex]\theta = sin^{-1}x[/itex]

    [itex]sin\theta = x[/itex]

    If the sine angle is X, then the opposite is X and the hypotenuse 1.

    the adjacent side can now be calculated using pythagoras, which gives [itex]\sqrt{1-x^2}[/itex]

    The cosine angle is the quotient of the adjacent and the hypotenuse:

    [itex]\sqrt{1-x^2} / 1[/itex]
     
  9. May 30, 2012 #8
    Would you care explaining me how you multiplied out what's rooted?

    I know sin(sin^-1) cancel out because you add the indices, so shouldn't that leave sin x..
     
    Last edited: May 30, 2012
  10. May 30, 2012 #9
    Those are inverse functions, so they don't simplify like exponents do.
    Since sinx and sin-1x are inverses and sin2x = (sinx)2, sin(sin-1x) = x and
    sin2(sin-1x) = (sin(sin-1x))2 = x2
     
  11. May 30, 2012 #10

    Mentallic

    User Avatar
    Homework Helper

    No, don't think of it that way. Inverse functions are a fancy word of saying "doing the opposite". You have some function, such as [itex]y=\sin(x)[/itex] and you want to make a process to get back to just x, and for this case its inverse will be [itex]\sin^{-1}(y)[/itex].
    Other inverses are, for example, the inverse of [itex]y=x^2[/itex] is [itex]\sqrt{y}[/itex] because [itex]\sqrt{x^2}=x[/itex] (technically it's |x| so that's why we specify domains, in this case [itex]x\geq 0[/itex])
    Another would include [itex]y=\ln(x)[/itex] and [itex]e^y[/itex]

    Also, keep in mind that if you have a function [itex]y=x^n[/itex] and applying its inverse [tex]\sqrt[n]{y}=y^{1/n}[/tex] the reason we get back to x is because [tex]\left(x^n\right)^{1/n}=x^{n\cdot\frac{1}{n}}=x^{\frac{n}{n}}=x[/tex]

    You multiply the indices, not add.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook




Similar Discussions: Prove cos(sin^-1 x)= [itex]\sqrt{1-x}[/itex]
  1. Sin(x) + cos(x) (Replies: 4)

Loading...